BUSINESS MARKETING STRATEGY OF SEAFOOD PROCESSED SOUVENIR DURING THE COVID-19 PANDEMI - Eni Karsiningsih, Anisa; Rufti Puji Astuti (Research Parks Publishers, 2023)
This study aims to determine the difference in profits before and during the covid-19 pandemic and to find out the marketing strategy for processed seafood souvenir businesses during the covid-19 pandemic. The research method used in this study is a case study. The differences in profits before and during the Covid-19 pandemic were analyzed by Wilcoxon analysis. While the marketing strategy for processed seafood souvenirs is analyzed using SWOT and followed by QSPM analysis to determine priority strategies. The results showed that there were significant differences in the profits of the business of processed seafood souvenirs before and during the Covid-19 pandemic. The business of seafood processed food souvenirs is in quadrant 1 position (growth oriented strategy). The results of the SWOT analysis recommend that companies carry out a Strength-Opportunity (SO) strategy including four alternative strategies which are then sorted by the QSPM matrix to obtain priority strategies. The results of the QSPM matrix are (1) providing affordable prices/maintaining prices to increase business activities and increase promotional activities to attract consumers with the highest TAS score of 7.54; (2) Strategies to maintain and improve the quality of products and services in order to make consumers loyal with a TAS score of 7.51; (3) The strategy of maintaining relationships or establishing cooperation with suppliers/suppliers or competitors with a score of 7.5; (4) The strategy of maximizing a strategic location in providing good services and facilities with a score of 7.48.